Initial surge in news use around coronavirus in the UK has been followed by significant increase in news avoidance - Kalogeropoulos, A; Fletcher, R; Nielsen, RK (Reuters Institute for the Study of Journalism, 2020)
In this RISJ Factsheet we examine news avoidance during the coronavirus pandemic in the UK. This is the third in a series of ten factsheets based on an ongoing online panel survey of a representative sample of the UK population, fielded from 7 May to 13 May 2020. We find that: (i) there has been a significant increase in news avoidance, with 22% saying they often or always actively try to avoid the news (up from 15% in mid-April), (ii) women (26%) are more likely to avoid news than men (18%), compounding existing gender inequalities in news use, (iii) the vast majority of those who always or often avoid news (86%), say they are trying to avoid COVID-19 news at least some of the time, with most primarily worried about the effect it has on their mood (66%).